Removal of phenol from water by adsorption. - Roostaei, Nadia. (University of Ottawa (Canada), 1999)
Phenol and its derivatives are compounds that are found in many industrial wastewaters such as in paint, paper, plastics, oil and gasoline, steel, textile, and wood industries. They are considered as toxic to humans and aquatic life. A minute concentration of phenol (2.5 ppm) causes objectionable taste in potable water. In this study, liquid phase adsorption of phenol from water has been investigated. Kinetic and equilibrium experiments have been performed for several adsorbents. The influence of particle size, temperature, and thermal regeneration on adsorption were also evaluated. The effect of temperature on adsorption was studied by determining equilibrium isotherms for HiSiv 3000 (Particle size = 50 x 70 mesh) at 25, 40, and 55°C. Thermal regeneration was performed for HiSiv 3000 at 360°C, and the results were compared with the regeneration efficiency of activated carbon obtained from literature. Two kinetic models were studied and applied to kinetic data for activated carbon, F-400, and HiSiv 3000 (four different particle sizes). Rates of adsorption and diffusion coefficients were determined by applying these models to the initial rapid stage of adsorption. Three equilibrium isotherm models were also examined for the above-mentioned adsorbents. (Abstract shortened by UMI.)
Keywords: Engineering, Chemical.